2001
DOI: 10.1126/science.1062538
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Resistance to STI-571 Cancer Therapy Caused by BCR-ABL Gene Mutation or Amplification

Abstract: Clinical studies with the Abl tyrosine kinase inhibitor STI-571 in chronic myeloid leukemia demonstrate that many patients with advanced stage disease respond initially but then relapse. Through biochemical and molecular analysis of clinical material, we find that drug resistance is associated with the reactivation of BCR-ABL signal transduction in all cases examined. In six of nine patients, resistance was associated with a single amino acid substitution in a threonine residue of the Abl kinase domain known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
2,121
1
42

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,878 publications
(2,188 citation statements)
references
References 31 publications
24
2,121
1
42
Order By: Relevance
“…49), in cardiomyocytes, and found that it partially rescued the cells from imatinib-induced toxicity 4 . Because ABL is known to induce apoptosis, the fact that it seemed to provide a survival signal in cardiomyocytes was surprising.…”
Section: R E V I E W Smentioning
confidence: 99%
“…49), in cardiomyocytes, and found that it partially rescued the cells from imatinib-induced toxicity 4 . Because ABL is known to induce apoptosis, the fact that it seemed to provide a survival signal in cardiomyocytes was surprising.…”
Section: R E V I E W Smentioning
confidence: 99%
“…23 The most common cause of secondary imatinib resistance is point mutations in BCR-ABL that prevent effective binding of imatinib but may retain kinase activity. [35][36][37][38][39] These mutations are clustered primarily within the kinase domain of BCR-ABL (ABL exons 4-10). 40 They exhibit differential relative resistance to imatinib in vitro.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…However, acquired resistance to imatinib develops in a substantial fraction of patients. In 70 -80% of these cases, acquired resistance is caused by point mutations in the ABL kinase domain (Gorre et al, 2001). So far, about 40 different point mutations have been discovered, each of which is sufficient to cause resistance to imatinib (Branford et al, 2003a).…”
Section: Dynamics Of CMLmentioning
confidence: 99%